Inside Cover: Synthesis and Application of Hydride Silica Composites for Rapid and Facile Removal of Aqueous Mercury (ChemPhysChem 18/2013). Issue 18 (16th December 2013) - Katok, Kseniia V.; Whitby, Raymond L. D.; Fayon, Franck; Bonnamy, Sylvie; Mikhalovsky, Sergey V.; Cundy, Andrew B.
<x xml:space="preserve">Abstract</x> Mesoporous hydride silica sorbents that exhibit rapid redox removal of ionic mercury from aqueous solutions are presented on p. 4126 ff. by K. V. Katok et al. and suggested as potential candidates for materials that can be used for mercury decontamination in natural waters and industrial effluents.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>